Effect of Acacia mangium canopy on physicochemical characteristics and nutrient concentrations of the soil at Ayer Hitam Forest Reserve, Malaysia - Sheip, Younes H Solaiman; Abdul Hamid, Hazandy; Abiri, Rambod; Saleh Japri, Mohd Nazre; Mohamed, Johar; Jalil, Abd Majid; Naji, Hamid Reza (Multidisciplinary Digital Publishing Institute, 2021)
The establishment of an Acacia mangium plantation often alters physicochemical characteristics and nutrient concentrations of soils. We aimed to evaluate the invasive potential of A. mangium forest on the soil in Ayer Hitam Forest Reserve, Peninsular, Malaysia. To achieve the mentioned target, four different regions, namely, the open ground region (OG), Acacia mangium region (AM), transition region (TZ), and native forest region (NF), were selected and each of the regions was divided into six plots. Composite samples were randomly taken from subplots at 0–15 cm depth (topsoil) and 15–30 cm depth (subsoil). Some physicochemical properties such as soil moisture and texture, textural classification, bulk density and particle density, pH, electric conductivity (EC), exchangeable bases (EB) (Ca, Mg and K), cation exchange capacity (CEC), organic matter (OM), total nitrogen (TN), and available phosphorous (Av. P) were analyzed. The results of our study showed that the soil of the AM region, which was clay loam, contained clay (51%), silt (32%), and sand (16%). The chemical analysis of topsoil showed significant differences in terms of OM%, exchangeable- Ca, Mg, K (molc kg−1), N (%), gravitational water content (GWC), and Avail. P between all four regions. Additionally, the highest pH and OM of topsoil were seen in the AM region with 4.5% and 4.33%, respectively. In the subsoil, there were significant differences (p ≤ 0.01) in terms of EC (ds/m), OM (%), Exchangeable- Ca, Mg and K (cmolc kg−1), GWC, available phosphorus, and N (%) between all four regions. The highest GWC, N (%), and Ca (cmolc kg−1) were observed in the AM region with 16.00, 0.14%, and 0.64 cmolc kg−1, respectively. These results showed that A. mangium changed some soil characteristics due to its invasion potential. In summary, A. mangium showed high adaptability on degraded forest land and high ability to accumulate the soil physicochemical properties to enhance its growth.